Edugame development for introduction chord basic guitar. Issue 3 (March 2021) - Tresnawati, D; Latifah, A; Satria, E; Rayahu, S
Abstract: Playing guitar is one of the activities that can hone the brain's ability and emotions. Learning to play guitar can be done directly or indirectly. Learning indirectly can be done using several media. One of them is by using a game application on a mobile device. The purpose of this study is to build an android based chord basic guitar learning game application. The methodology used the Digital Game Base Learning-Instructional Design, which consists of four stages: analysis, design, development, and quality assurance. The results showed that the basic guitar chord educational game could be used to facilitate the learning process for individuals who are currently or will be learning guitar. Also, additional facilities, namely the try-it feature in the bonus round, can stimulate users to directly practice the results of learning basic guitar chords into a song that has been provided ac-cording to the chord that has been taught before.